2005
DOI: 10.1354/vp.42-3-357
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Seminoma with Metastasis, Sertoli Cell Tumor, and Pheochromocytoma in a Spotted Dolphin (Stenella frontalis) and Malignant Seminoma with Metastasis in a Bottlenose Dolphin (Tursiops truncatus)

Abstract: Seminoma with metastasis was diagnosed in a spotted dolphin (Stenella frontalis) and an Atlantic bottlenose dolphin (Tursiops truncatus). Sertoli cell tumor and pheochromocytoma were also diagnosed in the spotted dolphin. The spotted and bottlenose dolphins were adult males that stranded and died on the coasts of northwest Florida and southeast North Carolina, respectively. Neoplasia is infrequently reported in cetaceans. This is the first report of seminoma, Sertoli cell tumor, and pheochromocytoma in a dolph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
10
0
1
Order By: Relevance
“…27 A stranded spotted dolphin was found to have metastatic testicular seminoma, adrenal pheochromocytoma, and a Sertoli cell tumor; there was no data on SDHB immunohistochemistry. 28 Our observations and these reports suggest that seminoma may be an infrequent component of the SDH tumor syndrome, and additional studies are needed to further explore this connection.…”
Section: Discussionmentioning
confidence: 60%
“…27 A stranded spotted dolphin was found to have metastatic testicular seminoma, adrenal pheochromocytoma, and a Sertoli cell tumor; there was no data on SDHB immunohistochemistry. 28 Our observations and these reports suggest that seminoma may be an infrequent component of the SDH tumor syndrome, and additional studies are needed to further explore this connection.…”
Section: Discussionmentioning
confidence: 60%
“…by the University of Clinical signs in humans, dogs, and cats can include Illinoisʼs Zoological Pathology Program Molecular headache, hypertension, weakness and collapse, Diagnostic Laboratory and were negative. exercise intolerance, gastrointestinal distress, car-Skeletal preparation revealed that thoracic ver-diac arrhythmias, anxiety and pacing (McNiel & tebrae nine and ten were fused with complete loss Husbands, 2005), agitation, tachypnea and hyphaof the intervertebral disc spacing. The transverse ema in cats (Wimpole et al, 2010), lethargy, and and spinous processes exhibited roughening of the tachyarrhythmia and collapse in dogs (Gostelow surface with boney loss and sites of boney prolif-et al, 2013).…”
Section: Postmortem Examinationmentioning
confidence: 99%
“…Morphological differences have been found between white-beaked dolphins of the eastern and western Atlantic (Mikkelsen & Lund, 1994). The genus Lagenorhynchus is believed to be a polyphyletic taxon (Cipriano, 1997;LeDuc et al, 1999;McGowen, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The potential for metastatic testicular neoplasia in cetaceans has been reported by Estep et al (2005). In that report, 2 cases of seminomas extended to retroperitoneal lymph nodes.…”
mentioning
confidence: 94%
“…Cowan et al (1986) and Geraci et al (1987) described 2 cases of interstitial (Leydig) cell tumor in common dolphins Delphinus delphis. Estep et al (2005) reported a seminoma with metastasis to a retroperitoneal lymph node and a Sertoli cell tumor in a spotted dolphin Stenella frontalis, in which a pheochromocytoma was concomitantly observed, and a seminoma with metastasis to the mesentery in a bottlenose dolphin.…”
mentioning
confidence: 99%